Assessment of Dental, Oral, and Nutritional Health Condition in Rejomulyo - Christinne Triwidawati; Lintang Mega Pertiwi; Dorisna Prijaryanti; Widy Jatmiko (NuCSJo : Nusantara Community Service Journal, 2025)
Dental and oral health play an important role in determining individual’s well being and quality of life. The appropriateness of dietary intake as shown by Body Mass Index (BMI) is a factor that influences dental and oral health. The objective of this community services is to identify health issues and improve awareness regarding dental health, oral hygine, and nutrition among the society in Rejomulyo. This activity employs observation, data collecting, material preparation, and the execution of health education. The observation phase revealed that dental and oral health in Rejomulyo exhibited a middling state, with 32% of respondents classified as obese. The outcomes of the education activities indicate an enhancement in respondent’s knowledge of dental, oral, and nutrition.